2018
DOI: 10.1097/ta.0000000000001704
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the traditional day and night shift in an acute care surgery fellowship: Is the swing shift a better choice?

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, at our facility, in recent years, we have given the option to trauma surgery fellows to work a “swing shift” from noon to midnight. This option has been successful in exposing these fellows to a higher number of adult patients and operative cases 10 . We have also observed, at our institution, that the swing shift tends to expose trainees to higher acuity adult patients than the day or night shift.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…However, at our facility, in recent years, we have given the option to trauma surgery fellows to work a “swing shift” from noon to midnight. This option has been successful in exposing these fellows to a higher number of adult patients and operative cases 10 . We have also observed, at our institution, that the swing shift tends to expose trainees to higher acuity adult patients than the day or night shift.…”
Section: Discussionmentioning
confidence: 56%
“…This option has been successful in exposing these fellows to a higher number of adult patients and operative cases. 10 We have also observed, at our institution, that the swing shift tends to expose trainees to higher acuity adult patients than the day or night shift. We specifically assessed the pediatric trauma volume of the swing shift in our study.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, alternative solutions exist. Trauma volume per trainee can be optimized via deliberate trainee scheduling, 21,22 focusing on the busier times of the day or the year, and use of a competency-based curricular model to minimize variability. These modifications can be further supplemented by increased use of simulation, both resuscitative and operative, and curricular innovation.…”
Section: Discussionmentioning
confidence: 99%
“…Chestovich et al found innovative scheduling to maximize patient numbers in light of work hour restrictions effective. 3 Surgical fellows increased their patient exposure when their program added a swing shift during the busiest trauma census hours. Using modeling of hourly volume trends allowed the program to match fellows with patient volume.…”
Section: Schedulingmentioning
confidence: 99%